Analisis variasi genetik anopheles subpictus(diptera: culicidae) dl sekitar Yogyakarta dengan RAPD-PCR =Analysis on Genetic Variations of Anopheles subpictus (Diptera: Culicidae) using RAPD-PCR in the Vicinity of Yogya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Up to present time, malaria still constitutes a major health problem in Indonesia, including in Java or outside the island. The presence of unidentified sibling (or closely related) species complex may result in difficulties or failure of the disease control program. The members of sibling species complex may posses different properties as phenotypical expressions of genetic variations owned by the reproductively isolated populations. This research was carried out primary to investigate the genetic variations of An. subpictus, mosquitos known as one of the main vector of malaria in Java, and to identify whether the genetic variations had become inter-specific. An. subpictus mosquito samples were collected using aspirator from different environment areas around Yogyakarta, i.e. coastal of Congot and Sanden, in Kulonprogo and Bantul regency, respectively, and inland hilly areas of Salaman with altitude of 300 m above sea level, and higher Sawangan with altitude of 700 m in Magelang regency. To investigate the genetic variations of mosquitos, RAPD-PCR method was adopted using oligo-nucleotide (10 base) random primers. This research included field and laboratory works: Anopheline mosquitos were collected, identified and sorted morphologically by their species. The DNA of An. subpictus mosquitos were the isolated (to be extracted, precipitated and washed), subsequently amplified using thermocycler (denaturated at 94Â°C